Hedging w zarządzaniu ryzykiem należności dewizowych - Jędrzejczyk, Marcin (Hedging transaction in risk management of receivables, 2008)
This paper presents the practical approach to the hedging transactions in the aspect of receivables management. The analysis is based on the exchange rate theory and productivity ratio. The prospective aspect of the research constitutes a fundamental premise to the process of decision making with foreign currency transactions. The main attention should be drawn to the determinants of the ex-change rate shaping, which can allow conducting the forecast in the assumed time horizon. Thus, the accurate forecast is treated as the necessary condition to engage into hedging transactions, which can successfully protect form exchange rate fluctuation risk.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 113-122